A Study on the level of satisfaction in the usage of digital wallet among the students in UiTM Puncak Alam / Nur Laila Khalidah Norhamly. - Norhamly, Nur Laila Khalidah (2019)
Digital wallet has been gaining its popularity alongside with the development in technology for payments system in providing convenience towards the consumer in Malaysia. The government has been started to promote the use of digital wallet towards every level of age but of course the one that will frequently use is the youth. The methodology that have been used for this research is the quantitative method through a survey that have been distributed among the age range of youth. The rising numbers of digital wallet can be seen as one of the proof that the Malaysian has been started to accept and put their trust in this method of payment system. Almost every stalls not only in big shopping malls but also a standard hawkers and stalls already accepted the use of digital wallet in doing any transactions. Most of the transactions that use digital wallet will receive discounts, promotions and even cash back as a reward towards the user. To see whether the users of digital wallet is satisfied with the services provided, limited studies has been conducted among the students in UiTM Puncak Alam specifically the residents in Angsana 2 College.